Development of Discord-Based Career Information Service Management Model to Improve Students’ Career Planning Ability - Dwikurnaningsih, Yari; Melisa, Ira; Waruwu, Marinu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop a Discord-based career information service management model to enhance students’ career planning abilities. This research method used research and development with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The developmental research was conducted at SMA Muhammadiyah Plus Salatiga, with teachers and students as the research subjects. The results of the study were validated using technical triangulation and source triangulation techniques. Data analysis utilized the interactive model for qualitative data and descriptive analysis for quantitative data. The IT expert validation resulted in a score of 92%, and the management expert validation yielded 90%. Additionally, the average trial results for teachers and students were 95.5% and 97.5%, respectively. Based on these findings, the development was categorized as excellent, feasible, and acceptable and can be utilized to enhance student’s career planning abilities.